Effect of High Heeled Shoe Sole to the Vertical Jump Performance of Volleyball Women Student Athletes - Olivar, Arjay Maiquez; Reyes, Jomel Nasayao; Balisi, John Paul Taguba; Panganiban, Teejay Dela Cueva (Physical Education and Sports: Studies and Research, 2024)
Background: The study investigates the effect of wearing high heeled shoe soles on the vertical jump performance of volleyball women student athletes compared to their performance in standard footwear. This research aims to address the problem of whether high heeled shoe soles negatively affect vertical jump ability, which is a critical factor in their sport performance. Objectives: This study investigated the influence of high heeled shoe soles on female volleyball athletes' vertical leap performance. Methods: Using a quasi-experimental design, the study included 15 female volleyball student-athletes from Batangas State University TNEU JPLPC-Malvar Campus in 2023-2024. Participants performed vertical jump tests under two conditions—wearing high heeled shoe soles and standard footwear—over two weeks, with three attempts per condition. Paired t-tests assessed performance differences between the two footwear types. Results: Results indicated that wearing high heeled shoe soles significantly improved jump heights, with average increases of 2.13 inches initially and 3.6 inches in post-tests. Statistical analysis yielded t-test values of 35.87 for pre-performance and 697.14 for post-performance, both showing significant gains. Conclusion: The study concludes that high heeled shoe soles positively influence vertical jump performance in female volleyball athletes, suggesting that this footwear could enhance athletic outcomes.